2008
DOI: 10.1002/macp.200800265
|View full text |Cite
|
Sign up to set email alerts
|

Poisson's Ratio of Monodomain Liquid Crystalline Elastomers

Abstract: Monodomains of smectic C liquid crystalline elastomers were prepared by controlled stretching of a polydomain thin film. Specimens were prepared from this film for stress–strain study. A Poisson's ratio of zero was found at small strains for uniaxial stretching perpendicular to the director. For uniaxial strain parallel to the director, Poisson's ratios of approximately 0.4–0.5 were found (by extrapolation) for very small strains. A modulus anisotropy of 8 was found for stretching parallel versus perpendicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 20 publications
(21 reference statements)
3
45
0
Order By: Relevance
“…Polydomain smectic MCLCEs have been extensively studied [20,[60][61][62][63][64][65][66][67]. Sánchez-Ferrer et al [64] reported the polydomain to monodomain (P-M) transition caused by uniaxial strain in these materials.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
See 2 more Smart Citations
“…Polydomain smectic MCLCEs have been extensively studied [20,[60][61][62][63][64][65][66][67]. Sánchez-Ferrer et al [64] reported the polydomain to monodomain (P-M) transition caused by uniaxial strain in these materials.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
“…Three specimens of LCE1 were prepared: one in polydomain and the other two in mechanically induced monodomain states. An initial strain of 200% (λ = 3) was applied and approximately 130% of the strain was retained in the monodomain samples for prolonged periods of time [65]. Figure 7 shows the response characteristics of LCE1 when stretched along the directions parallel and perpendicular to n n , and also in the initially polydomain state.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
See 1 more Smart Citation
“…The curve illustrated here is jagged because the alignment of each domain jumps at a slightly different threshold. The expansion of the film thickness and the energy loss as a result of the jump in the director orientation in this geometry may be observable in experiments on pseudo-monodomains [11,48]. The larger values of deformation reported in experiment before the knee in the stress-strain curve point to a much larger value of α than in the illustrative plot in Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The small strain induced in the liquid crystal surface agreed with the Poisson's ratio under small strain theory. Therefore, Hookean's law and small strain theory (Poisson's ratio) [20][21] were applied to compute the forces required in inducing the deformation lines in the liquid crystal surfaces. The equation in determining the Young's modulus of a linear elastic material through the relationship of stress-strain established by Hooke's law is as follows:…”
Section: Cell Relaxation Experiments and Quantification Of Cell Tractimentioning
confidence: 99%